Monitoring the Dissolution and Hydrolysis of Pyrosulfate by Electrochemistry at a Liquid-Liquid Microinterface Array - Henares, Terence G.; Gale, Julian; Herzog, G.; Arrigan, Damien (WILEY-V C H VERLAG GMBH, 2022)
Dissolution and hydrolysis processes are important in a variety of settings, including industrial and environmental applications. In this work, the hydrolysis of pyrosulfate (disulfate) was investigated by ion-transfer electrochemistry at an array of microinterfaces between two immiscible electrolyte solutions (μITIES). Current associated with pyrosulfate transfer was observed, but it decreased with time. This is due to the hydrolysis of pyrosulfate to hydrogen sulfate and sulfate. Corroborating data for the hydrolysis was obtained from pH measurements (acidification of the aqueous solution) and Raman spectroscopy (formation of sulfate and hydrogen sulfate). Measurement of the ion-transfer potential from the voltammograms enabled estimation of pyrosulfate's Gibbs energy of transfer between the phases. Quantum mechanical calculations were employed to estimate the thermodynamics for the reactions of pyrosulfate, hydrogen sulfate and sulfate, which supported the experimentally observed trends. Altogether, these results illustrate the use of electrochemistry at the μITIES to characterise dissolution and hydrolysis processes.